Efficacy and safety of traditional Chinese medicine (TCM) combined with immune checkpoint inhibitors (ICIs) for the treatment of cancer: a systematic review and meta-analysis - Ke, Yani; Pan, Yuyan; Huang, Xueru; Bai, Xing; Liu, Xiaojuan; Zhang, Mingsi; Wei, Yunhai; Jiang, Tao; Zhang, Guangji (Frontiers in Pharmacology, 2025)
BackgroundCancer remains a major global health burden. Combining traditional Chinese medicine (TCM) with immune checkpoint inhibitors (ICIs) may potentially mitigate treatment-related side effects and improve the quality of life for cancer patients. To critically evaluate the clinical efficacy of this combination therapy, a meta-analysis was performed.MethodsA systematic search was conducted across six databases. Data were analyzed using RevMan 5.3 and Stata 12. Heterogeneity was explored through subgroup analysis and meta-regression. The robustness of results was assessed via sensitivity analysis and publication bias.Results41 studies were included. The TCM + ICIs group demonstrated significantly superior outcomes compared to the ICIs group across multiple endpoints: Overall Response Rate (ORR) (RR: 1.34 [1.20, 1.49]), Disease Control Rate (DCR) (RR: 1.15 [1.10, 1.21]), CD4+/CD8+ T-cell ratio (WMD: 0.25 [0.15, 0.35]), Progression-Free Survival (PFS) (WMD: 0.96 [0.29, 1.63]), Overall Survival (OS) (WMD: 1.46 [0.62, 2.30]), Karnofsky Performance Status (KPS) (WMD: 6.35 [4.99, 7.70]), and TCM Therapeutic Evaluation (RR: 1.42 [1.30, 1.55]). Conversely, the TCM + ICIs group showed lower levels of tumor markers, including Alpha-Fetoprotein (AFP) (SMD: 0.75 [-1.49, −0.01]), Carcinoembryonic Antigen (CEA) (SMD: 0.72 [-1.08, −0.37]), Carbohydrate Antigen 125 (CA125) (SMD: 0.77 [-1.46, −0.08]), and a reduced incidence of adverse events (RR: 0.82 [0.69, 0.97]). There is high heterogeneity among CD4+T/CD8+T studies due to the type of tumor and whether it is combined with chemotherapy. The high heterogeneity among studies on KPS may be related to the type of ICIs. Sensitivity analysis and assessment of publication bias confirmed the robustness of the pooled results.ConclusionThe combination of TCM with ICIs appears to enhance antitumor immunity, reduce adverse reactions, lower serum tumor marker levels, improve disease control, and ameliorate patient performance status. This combination strategy represents a promising therapeutic approach for various cancers and warrants further investigation.